Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1976
DOI: 10.1080/00288306.1976.10426309
|View full text |Cite
|
Sign up to set email alerts
|

Microseismicity and geologic structure in the northern South Island, New Zealand

Abstract: Locations, rates of occurrence, and composite focal mechanisms of microearthquakes in the Marlborough region are used to examine the tectonics of the region. Earthquakes in the upper crust reflect regional compression along ,an axis trending NW to WNW; their strike-slip and thrust mechanisms can be related to the regional geofogy. Seismicity deeper than about 20 km trends obliquely to the structural grain and appears to be intimately related to an underlying Benioff zone. Earthquakes in the 20-35 km depth rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1
1

Year Published

1977
1977
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 46 publications
3
39
1
1
Order By: Relevance
“…Microearthquake surveys carried out in 1972, 1973(Arabasz & Robinson 1976), 1975(Kieckhefer 1977, and during the period October 1993 to March 1994(EberhartPhillips & Reyners 1997) also reflect the general trends observed by Anderson & Webb (1994). The 1972 survey found that moderate amounts of activity were still occurring in the aftershock zones of the 1968 Inangahua and 1971 Maruia earthquakes (D and F, Fig.…”
Section: Regional Seismicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Microearthquake surveys carried out in 1972, 1973(Arabasz & Robinson 1976), 1975(Kieckhefer 1977, and during the period October 1993 to March 1994(EberhartPhillips & Reyners 1997) also reflect the general trends observed by Anderson & Webb (1994). The 1972 survey found that moderate amounts of activity were still occurring in the aftershock zones of the 1968 Inangahua and 1971 Maruia earthquakes (D and F, Fig.…”
Section: Regional Seismicitymentioning
confidence: 99%
“…All focal mechanisms are equal area projections of the upper focal hemisphere. 174" from microseismic surveys (Arabasz & Robinson 1976;Kieckhefer 1977;Eberhart-Phillips & Reyners 1997). Anderson et al (1993) suggested that this contrast in deformation has resulted from a change in plate-motion direction during the late Oligocene to early Miocene, which required a component of shortening to be accommodated.…”
Section: Tectonicsmentioning
confidence: 99%
“…The Glasgow Fault of Buller was active in a thrusting-sinistral sense during the May 1968 Inangahua earthquake (Lensen & Otway 1971). Such faulting is considered general for major faults west of Alpine Fault (Arabasz & Robinson 1976); however, regional compression, northwest-southeast, is like that for much of New Zealand (Robinson & Arabasz 1975). Elements of a sinistral wrenchfault system (Harding 1974) are not well developed; most folds and the major faults are parallel, and the structure is probably the result of shortening in the basement (as is suggested by the present day direction of the principal horizontal stress, L3.ircl 1968).…”
Section: Structurementioning
confidence: 99%
“…1), using geomorphological and seismological methods. Previous work in the region includes reconnaissance geological mapping by Bowen (1964) and Lensen (1962) and microearthquake surveys in 1972 and 1973 by Arabasz & Robinson (1976). Analysis of triangulation data to determine earth strain rates near the Marlborough coast has been carried out by Bibby (1976) and strain measurement throughout New Zealand continues under a programme run by the Earth Deformation Studies (EDS) section of the N.Z.…”
Section: Introductionmentioning
confidence: 99%
“…Bibby (1976) has used triangulation data to find that strain accumulation near the Marlborough coast is approximately 0'4 microradian/yr, with an axis of principal horizontal shortening (PHS) striking approximately 110° east of north. Arabasz & Robinson (1976) are from Bowen (1964), Lensen (1962), and the author's surveys. Two significant antecedent earthquakes are also indicated: a 1973 event near the Clarence Fault and an event 21· 5 days before the start of the survey, 9 km to the south of the mapped region.…”
Section: Introductionmentioning
confidence: 99%